1984
DOI: 10.1177/073168448400300105
|View full text |Cite
|
Sign up to set email alerts
|

Model for Predicting the Mechanical Properties of Composites at Elevated Temperatures

Abstract: A model is presented for predicting the changes in the mechanical properties of organic matrix composites exposed to elevated temperatures. The model can be used to calculate changes in the tensile, compressive and shear strengths and moduli as functions of exposure time. The model also provides the decrease in the stress ratio with time and the time of failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…Dutta and Hui (2000) related the current elastic modulus to the current temperature as well as the current mass density of the composite. The early model by Springer (1984) related current material properties to the loss of mass density. In Bai et al (2008), who considered different material states in different temperature ranges, a kinetic theory was employed to model the degradations of stiffness, viscosity, and the coefficient of thermal expansion.…”
Section: Temperature Distributionmentioning
confidence: 99%
“…Dutta and Hui (2000) related the current elastic modulus to the current temperature as well as the current mass density of the composite. The early model by Springer (1984) related current material properties to the loss of mass density. In Bai et al (2008), who considered different material states in different temperature ranges, a kinetic theory was employed to model the degradations of stiffness, viscosity, and the coefficient of thermal expansion.…”
Section: Temperature Distributionmentioning
confidence: 99%
“…Recent studies 7–11 have shown that composite materials significantly degrade when subjected to even relatively low levels of thermal loading. Efforts have been made in order to provide experimental and analytical techniques that could be used to predict when failure occurs in composite materials due to elevated temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed degradation mechanisms for environmental exposure are studied by Tsai [18] and Springer [19][20], but it is apparent that most of the models predicting temperature and moisture effects are based on empirical formulations which badly need test data. Moreover, the existing moisture and temperature induced degradation data are mostly for single fiber composites and property like Poisson's ratio is rarely studied under such influence.…”
Section: Introductionmentioning
confidence: 99%